In renal transplants with delayed graft function chemokines and chemokine receptor expression predict long-term allograft function - Dikow, Ralf; Becker, Luis Eduardo; Schaier, Matthias; Waldherr, Rüdiger; Groß-Weissmann, Marie-Luise; Zeier, Martin (Transplantation, 2010)
Background: Chronic loss of renal allograft function is associated with interstitial fibrosis and tubular atrophy (IF/TA). Independent of the underlying reason, one initial step in the development of fibrosis is chemokine-driven invasion of leukocytes from the blood vessels into the allograft. We studied the role of chemokines in kidney allografts with delayed graft function and the subsequent long-term outcome of renal function and fibrosis. - Methods: We examined repetitive biopsies of 30 patients without signs of acute rejection but with initially delayed graft function for IF/TA. In addition, we examined the expression of chemokine receptor (CCR)-1 and CCR2 on invaded leukocytes and macrophages and the corresponding ligands regulated upon activation, normal t-cell expressed, and secreted (RANTES) and monocyte chemotactic protein-1 on residential kidney cells. - Results: The initial expression of CCR1 positive invading cells and RANTES in glomerular cells correlated with the allograft function 12 months after transplantation and at last follow-up. The expression was independent of donor characteristics such as age, gender, infectious state, cause of death, or use of vasopressive agents. Furthermore, it did not correlate with the duration of cold ischemia time. Among the patients with the most progressive loss of allograft function follow-up biopsy specimen did not reveal any signs of rejection but showed increased CCR1 and RANTES expression in the interstitium suggesting ongoing inflammation and fibrosis. - Conclusion: An early expression of RANTES in renal allografts with delayed graft function with consecutive invasion of CCR1 positive cells seems to promote ongoing IF/TA and to worse renal allograft outcome.
Gesehen am 02.02.2023